2014
DOI: 10.4028/www.scientific.net/amr.881-883.776
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Purification and Partial Characterizations of Polysaccharides from <i>Gracilaria lemaneiformis</i>

Abstract: In the present study, the crude polysaccharides were extracted from the microalgae Gracilaria lemaneiformis with ultrasonic-assisted extraction method and purified by DEAE-52 cellulose chromatography and Sephadex G-100 size-exclusion chromatography in that order. Two main fractions, GPC-1and GPC-2, were obtained through the extraction and purification steps. Then partial characterizations, such as chemical composition, ultraviolet (UV) spectrum and infrared (IR) spectrum of the two fractions were analyzed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Polysaccharides from Gp. lemaneiformis (PGL) consist of 3,6-anhydro- l -galactose and d -galactose and are acidic polysaccharides with a linear structure of repeated disaccharide agarobiose units [ 11 ]. Since polysaccharide bioactivity is most closely related to their chemical composition, configuration, and molecular weight (MW), as well as their physical properties, we extracted and purified PGL using chromatography and partially characterized it using a series of chemical and instrumental analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides from Gp. lemaneiformis (PGL) consist of 3,6-anhydro- l -galactose and d -galactose and are acidic polysaccharides with a linear structure of repeated disaccharide agarobiose units [ 11 ]. Since polysaccharide bioactivity is most closely related to their chemical composition, configuration, and molecular weight (MW), as well as their physical properties, we extracted and purified PGL using chromatography and partially characterized it using a series of chemical and instrumental analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the structure and activities of some active polysaccharides in G. lemaniformis, they are considered as active antitumor agents. Polysaccharides having such structural similarities found in G. lemaniformis are 3,6-anhydro-L-galactose, D-galactose and some acidic polysaccharides with a linear structure of repeated disaccharide agarobiose units [83][84][85][86]. G. lemaniformis had potential antitumor activity and in a study, it was observed that G. lemaniformis extract showed strong antitumor activity through apoptosis-related Fas/FasL signaling pathway in the gastric cancer cell line MKN28, human lung cancer cell line A549 and mouse melanoma cell line B16.…”
Section: Pharmacological Prospectsmentioning
confidence: 99%
“…Thus, GPC gives the molecular weight distribution of a sample [125,147]. For microalgae, this technique is particularly useful in the characterization of polysaccharides [148,149] that can reach levels in the range of 8-64% DW [150] and polyhydroxyalkanoates [151].…”
Section: Gel Permeation Chromatographymentioning
confidence: 99%